A fun day out : a Tom and Holly story - Mitchelhill, Barbara (London : Macmillan Education, 2016)
Macmillan English Explorers is an exciting new reading programme developed specifically for children learning English in kindergartens and primary schools. Written with second language learners in mind, these books expose children to real language and develop their reading and vocabulary skills.
Keywords: Readers (Primary)